(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
Voltage stability has been a major concern for operators in recent years, particularly for power system that is highly loaded & have a reactive power deficit. The voltage instability is a significant danger to the protection, safety, and dependability of power systems. Due to limited resources, power production and transmission development has been insufficient in the past 10 years, even though power consumption has risen considerably. As a result, under high loads, existing transmission lines are utilized near their thermal stability limitations, and system stability becomes a power transfer limiting issue. Environmental, political, social, and regulatory limitations prevent significant development of generating and transmission systems to meet increasing demand. Flexible Alternating Current Transmission System (FACTS) controllers open the way to improved power systems control, at least for the transmissions line, in this context. FACTS technologies aids in the exploration of novel flow control options and enhances the operating capabilities of current and future transmission lines. This article provide a thorough examination of the main FACTS controllers and their applications.